DETERMINASI UTANG LUAR NEGERI DI INDONESIA (PERIODE TAHUN 1990-2021) - Nurfitriana, Nurfitriana; Rizki, Darlin (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The country in developing its economy cannot be separated from debt, especially debt originating from abroad. This causes countries to depend on foreign debt from other countries, namely developed countries. This study aims to explain the determinants of foreign debt in Indonesia. The research method used is the Ordinary Least Square (OLS) method using annual time series data for 32 years from 1990-2021 and analyzed with the help of Eviews 10. Secondary data was obtained from the World Bank and Bank Indonesia (BI). The results of the study reveal that the Gross Domestic Product (GDP) has a positive and significant effect on Foreign Debt (ULN), Foreign Investment (PMA), and the exchange rate (KURS) has a negative and significant effect on Foreign Debt (ULN), as well as exports (EKS) has a negative and insignificant effect on Foreign Debt (ULN). Simultaneously, the variables PDB, FDI, EKS, and KURS have a positive and significant effect on Foreign Debt (ULN)